Clinical Profile of Patients with Ischaemic Heart Disease and its Correlation with Rheumatoid Factor: A Cross-sectional Study - Sachin Shivnitwar; Sandesh Sadanand Raut; Prasad Bagare; Priya Baluni; Shubhangi Kanitkar; ShreeVidya Yekkaluru (Journal of Clinical and Diagnostic Research)
Introduction: Ischaemic Heart Disease (IHD) remains a leading cause of global mortality, with increasing evidence suggesting the role of inflammatory markers in its pathogenesis. While Rheumatoid Factor (RF) is traditionally associated with autoimmune conditions, its potential involvement in IHD has gained attention. Aim: To evaluate the clinical profile of IHD patients and investigate its correlation with RF. Materials and Methods: A cross-sectional study was conducted at Dr. D. Y. Patil Medical College and Research Centre, Pune, Maharashtra, India from November 2023 to October 2024, involving 100 IHD patients. Comprehensive clinical assessments, including detailed history, physical examination, laboratory investigations (including RF testing), Electrocardiography (ECG), and cardiac imaging, were performed. Statistical analysis was conducted using Epi Info software version 7. Results: The study population (52% male, 48% female) showed a high prevalence of RF positivity (70%). Significant correlations were found between RF levels and cardiac parameters: a negative correlation with ejection fraction (r-value=-0.385, p-value=0.002) and positive correlations with the number of vessels involved (r-value=0.412, p-value=0.001) and C-Reactive Protein (CRP) levels (r-value=0.526, p-value <0.001). Traditional risk factors were prevalent: diabetes mellitus (52%), hypertension (40%) and dyslipidaemia (50%). Seventy-five percent of patients showed angiographic evidence of coronary artery disease, with 29% having triple vessel involvement. RF-positive patients demonstrated more severe disease manifestations across multiple parameters. Conclusion: A significant correlation was found between RF and IHD severity, suggesting its potential utility as a marker for risk stratification. The findings support the integration of RF testing in the comprehensive evaluation of IHD patients, particularly for identifying those at risk for more severe disease manifestations.